2009
DOI: 10.1108/02635570910982300
|View full text |Cite
|
Sign up to set email alerts
|

TQM and customer satisfaction in Malaysia's service sector

Abstract: Purpose-The purpose of this paper is to investigate the relationship between total quality management (TQM) practices and customer satisfaction (CS) as perceived by managers' perspectives in Malaysia's service sector. Design/methodology/approach-The data are collected from 140 managers of Malaysia's service firms. The structural analysis is conducted to test the hypotheses in this paper. Findings-Results reveal that leadership, customer focus, information and analysis, and human resource focus are found to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
97
1
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(118 citation statements)
references
References 59 publications
13
97
1
7
Order By: Relevance
“…Crosby concluded that TQM is helpful for improved resilience of senior executives and they should treat quality as their dominant responsibility. Leadership is an important part of TQM implementation because it gives the source of proper orientation, implementation and origin of whole quality activities (Prajogo et al 2004) (Singh 2006) (Saravanan R. 2007) (Teh 2008) (Sit 2009) (Teh 2009) ). Dale has also same thinking for senior management that they are the key initiators of Quality revolution which is termed as second industrial revolution by Kanji.…”
Section: Leadershipmentioning
confidence: 99%
“…Crosby concluded that TQM is helpful for improved resilience of senior executives and they should treat quality as their dominant responsibility. Leadership is an important part of TQM implementation because it gives the source of proper orientation, implementation and origin of whole quality activities (Prajogo et al 2004) (Singh 2006) (Saravanan R. 2007) (Teh 2008) (Sit 2009) (Teh 2009) ). Dale has also same thinking for senior management that they are the key initiators of Quality revolution which is termed as second industrial revolution by Kanji.…”
Section: Leadershipmentioning
confidence: 99%
“…U. S and Japanese gurus focused on the use of TQM in manufacturing sector as their primary work and secondary attention was given to adoptability of TQM in service sector but still there were many other people who were conducting research on use of TQM in service industry (Sureshchandra et al, 2002;Sit et al, 2009). There are some service sectors such as telecommunication, hospitals, banks, educational institutes and hotel organizations which are using TQM philosophy to improve the quality of service.…”
mentioning
confidence: 99%
“…The authors identified three "soft" TQM components representative of the overall TQM approach: continuous improvement and training, total employee empowerment and involvement, and quality driven culture. In a more recently published study, Sit et al (2009) surveyed managers from Malaysian service organizations and found human resources, leadership, and information analysis and knowledge management to be the TQM practices that had significant and positive correlations with customer satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%